Late-Onset Bilateral Choroidal Metastases from Clear Cell Renal Cell Carcinoma - Constantinos D. Georgakopoulos; Athina Pallikari; Panagiotis Plotas; Olga E. Makri (Case Reports in Urology)
Aim. To present a case of clear cell renal cell carcinoma with late-onset bilateral choroidal metastases. Case Report. A 57-year-old male patient in the Oncology Clinic complained of reduced vision in the right eye (OD) for 7 days. The patient, who was under immunotherapy with nivolumab, had been diagnosed with clear cell renal cell carcinoma in the left kidney 15 years ago that recurred in the right kidney before 2 years. Metastases in the brain, lungs, and bones had also been diagnosed. On ophthalmological examination, the visual acuity was 20/50 OD and 20/20 in the left eye (OS). Dilated fundus examination in OD revealed a single raised oval-shaped yellowish choroidal nodule infratemporally with macular involvement. A similar lesion, sparing the macula, was observed in OS. Fundus autofluorescence revealed diffuse punctate hyperautofluorescence on the lesions. Serous macular detachment was also observed in OD. A standardized A-scan ultrasound demonstrated an irregular structure of the lesions with moderate to high internal reflectivity. Based on the history and clinical and echographic characteristics, the diagnosis of bilateral choroidal metastases from renal cell carcinoma was set. Conclusion. Choroidal metastases from the primary renal tumor are extremely rare. The time interval between primary malignancy and choroidal metastasis is reported to be 12-96 months. Bilateral choroidal metastases have been described in 9 cases. We describe a rare case where bilateral choroidal metastases were diagnosed 15 years after the initial diagnosis of clear cell renal cell carcinoma.